Hubungan Minat Terhadap Hasil Belajar Matematika Peserta Didik Kelas V Sekolah Dasar, Gugus III, Kec. Batang Kapas Kab. Pesisir Selatan - Trisia, Vristi; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research is motivated by the low interest in learning mathematics and student learning outcomes. This study aims to determine whether there is a relationship between learning interest and learning outcomes of class V Cluster III students in Batang Kapas District. The method used is the correlational method. The sample study was all fifth-grade students at SD Negeri 03 Bukit Tambu Tulang, Batang Kapas District, Pesisir Selatan Regency, with a total of 30 students. Data collection techniques used are questionnaires, questions, observation, and documentation. Data analysis techniques using a manual formula with the help of Microsoft Excel, and the SPSS 16 computer program. From the data analysis performed, it was obtained a Pearson Correlation value of 0.415 and r-table with df = 81 at a 5% significance level of 0.361, which means that the count is greater than the r-table (0.415 > 0.361). The significance value of the linearity test obtained was 0.000, which was less than 0.05. This shows that there is a significant relationship between interest in learning and the learning outcomes of class V Cluster III students in Batang Kapas District.Keywords: Interest in Learning, Learning Outcomes, Mathematics